Stalin and the Origins of Mistrust - Milena Nikolova; Olga Popova; Vladimir Otrachshenko (Institute of Labor Economics (IZA), 2019)
We show that current differences in trust levels within former Soviet Union countries can be traced back to the system of forced prison labor during Stalin's rule, which was marked by high incarceration rates, repression, and harsh punishments. We argue that those exposed to forced labor camps (gulags) became less trusting and transferred this social norm to their descendants. Combining contemporary individual-level survey data with historical information on the location of forced labor camps, we find that individuals who live near former gulags have low levels of social and institutional trust. Our results are robust to a battery of sensitivity checks, which suggests that the relationship we document is causal. We outline several causal mechanisms and test whether the social norm of mistrust near gulags developed because of political repression or due to fear that inmates bring criminality. As such, we provide novel evidence on the channels through which history matters for current socio-economic outcomes today.
Keywords: D02; H10; N94; Z13; 330; social trust; institutional trust; trustworthiness; forced labor; economic history; former Soviet Union